2018
DOI: 10.4315/0362-028x.jfp-18-080
|View full text |Cite
|
Sign up to set email alerts
|

Radio-Frequency Processing for Inactivation of Salmonella enterica and Enterococcus faecium NRRL B-2354 in Black Peppercorn

Abstract: Several Salmonella outbreaks linked to black pepper call for effective inactivation processes, because current decontamination methods result in quality deterioration. Radio-frequency (RF) heating provides a rapid heating rate and volumetric heating, resulting in a shorter come-up time. This allows for choosing a high-temperature and short-time combination to achieve the desired inactivation with minimal quality deterioration. The objectives of this study were to evaluate RF heating for inactivation of Salmone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 39 publications
1
20
0
Order By: Relevance
“…The results in this study showed that Salmonella in milk powder experienced a rapid death rate in the first few weeks of storage followed by a slower death rate are in agreement with several published studies (LiCari and Potter, 1970;Lian et al, 2015). A similar reduction in Salmonella population has been observed during the postinoculation process of low water activity foods, such as black pepper (Wei et al, 2018(Wei et al, , 2019, cumin seeds (Chen et al, 2019), egg white powder (Wei et al, 2020b), almond (Abd et al, 2012), wheat flour (Forghani et al, 2019), and walnut kernel (Blessington et al, 2012). Salmonella cells need time to adapt to a low water activity environment.…”
Section: Survival Of Salmonella and E Faecium In Wmp And Nfdmsupporting
confidence: 92%
See 1 more Smart Citation
“…The results in this study showed that Salmonella in milk powder experienced a rapid death rate in the first few weeks of storage followed by a slower death rate are in agreement with several published studies (LiCari and Potter, 1970;Lian et al, 2015). A similar reduction in Salmonella population has been observed during the postinoculation process of low water activity foods, such as black pepper (Wei et al, 2018(Wei et al, , 2019, cumin seeds (Chen et al, 2019), egg white powder (Wei et al, 2020b), almond (Abd et al, 2012), wheat flour (Forghani et al, 2019), and walnut kernel (Blessington et al, 2012). Salmonella cells need time to adapt to a low water activity environment.…”
Section: Survival Of Salmonella and E Faecium In Wmp And Nfdmsupporting
confidence: 92%
“…Also, due to the difficulty of directly introducing the target pathogen into the processing plant, the use of a surrogate to replace the pathogen is recommended by FDA (2013) to conduct the validation study in the industrial processing plant. Several studies (Bianchini et al, 2014;Liu et al, 2018;Verma et al, 2018;Wei et al, 2018) have previously demonstrated that Enterococcus faecium NRRL B-2354 is a suitable surrogate for Salmonella during thermal processing of low water activity foods.…”
Section: Introductionmentioning
confidence: 99%
“…More applied RF cases have been developed in depth, although other authors asserted that a limitation of applied RF is undesirable non‐uniform heating . For all the reports of pasteurization using RF in a number of products, the study of RF sterilization of powder products is still scarce . And no work on pasteurizing barley grass powder has been reported, but more drying was conducted in other materials …”
Section: Introductionmentioning
confidence: 99%
“…The Salmonella enterica strains used in this study are shown in Table 2 and were kindly provided by Nathan Anderson (U.S. Food and Drug Administration, Institute for Food Safety and Health, Bedford Park, Illinois). The strains were selected because of their involvement in LMF-associated outbreaks and also because they have been employed in storage and thermal resistance studies ( 46 ). Media and conditions routinely used for growth include Trypticase soy broth (TSB) (Becton, Dickinson & Co., Sparks, MD) containing 0.6% yeast extract (TSB-YE) (Becton, Dickinson & Co.) and TSB-YE supplemented with 1.2% agar (TSA-YE) (Becton, Dickinson & Co.) incubated statically at 37°C for 24 h. Bacterial culture stocks were preserved in TSB containing 20% glycerol (Fisher Scientific, Fair Lawn, NJ) at −80°C.…”
Section: Methodsmentioning
confidence: 99%